THE ROLE OF TRAINING IN IMPROVING THE CAPACITY OF VILLAGE GOVERNMENT APPARATUS (A Study at the Village Government Training Center Office in Lampung, Ministry of Home Affairs) - Siti Susiati Ambri; Agus Purnomo (International Journal of Multidisciplinary Reseach, 2026)
The research method used is descriptive qualitative research. This method is used to describe the role of training in improving the capacity of village government apparatus (a study at the Village Government Office in Lampung, Ministry of Home Affairs). All data were obtained directly from informants in the field using interviews and document studies. The results of the study indicate that training plays a crucial role in improving the capacity of village government apparatus through the dimensions of knowledge, skills, attitudes and behavior, as well as leadership and management. Through planned and ongoing training, village apparatus can improve their understanding of regulations and policies, develop technical and service skills, develop professional attitudes and integrity, and strengthen leadership and management capabilities within village government organizations.